EFEKTIVITAS PEMBERIAN AIR REBUSAN Myrmecodia pendans TERHADAP JUMLAH SEL MAKROFAG PADA RADANG MUKOSA MULUT Rattus norvegicus - Mira Hartanti; Gunawan Wibisono; Rochman Mujayanto; Yayun Siti Rochmah (Jurnal Medali, 2013)
Inflammation of oral mucosa often occurs in the form of recurrent ulcers and on histopathological assessment proved infiltration of inflammatory cells such as polymorphonuclear cells and mononuclear phagocytes. Myrmecodia pendans contain flavonoids, polifenols, tokoferols that can heal inflammation. The purpose of this study is to determine the effectiveness differences in the provision of Myrmecodia pendans decoction to the number of macrophages in inflammation of oral mucosa Rattus norvegiccus with various concentrations.The research method used is an experimental design with post test control group design. The sample were 25 tails male Rattus norvegiccus were divided into 5 groups. Group I was given of Myrmecodia pendans decoction concentration 25%, Group II was given concentration 50%, Group III was given concentration 75% , Group IV was given concentration 100% and the control group was aquadest.Test results of the study based on the comparison between the five groups by One Way ANOVA showed that the average number of macrophages have significance differencess in all groups (p <0.05).Conclusions provision of Myrmecodia pendans decoction concentration 100% has the highest effectiveness of the number of macrophages than concentration 25%, 50%, and 75% in rats oral mucosa inflammation.Â Keywords : oral mucosa inflammation, macrophages, Myrmecodia pendans.